2011
DOI: 10.3109/19396368.2011.646047
|View full text |Cite
|
Sign up to set email alerts
|

Natural cycle is superior to hormone replacement therapy cycle for vitrificated-preserved frozen-thawed embryo transfer

Abstract: We undertook this retrospective variables-control analysis to compare the reproductive outcomes of frozen-thawed embryo transfer using endometrial preparation with either natural cycle or hormone replacement therapy cycle. Patients were divided into three subgroups. Subgroup A (n = 32) consisted of patients having three 8-cell post-thawed embryos transferred. Subgroup B (n = 404) consisted of patients having three good quality post-thawed embryos transferred. Subgroup C (n = 578) consisted of patients having t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
1
26
1
2
Order By: Relevance
“…In agreement with our findings, some previous studies observed superior outcomes in terms of implantation, clinical pregnancy, and lower miscarriage rates when natural cycles were used [Morozov et al 2007;Orvieto et al 2016;Xiao et al 2012]. Moreover, since FET during a natural cycle is less expensive and more patient-friendly, Peeraer et al [2015] recommended NC regimen as the treatment of choice for women with regular cycles undergoing FET.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with our findings, some previous studies observed superior outcomes in terms of implantation, clinical pregnancy, and lower miscarriage rates when natural cycles were used [Morozov et al 2007;Orvieto et al 2016;Xiao et al 2012]. Moreover, since FET during a natural cycle is less expensive and more patient-friendly, Peeraer et al [2015] recommended NC regimen as the treatment of choice for women with regular cycles undergoing FET.…”
Section: Discussionsupporting
confidence: 81%
“…For example, natural cycles with or without human chorionic gonadotropin (HCG) induced ovulation requires minimum medication and typically carried the least risk for adverse effects and is the least costly. Several groups have reported superior results for this regimen [Morozov et al 2007;Xiao et al 2012]. For the reason of convenience, artificial cycles are often applied to patients with regular menstrual intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, embryo cryopreservation was undertaken in patients with surplus embryos or patients with contraindications to transfer such as risk of OHSS or poor endometrial development and in some instances for fertility preservation. Recently, several groups have compared PR between embryos transferred during fresh-gonadotropin-stimulated-cycles versus FETs in a subsequent estrogenstimulated (synthetic) cycle [3,16] or under a natural cycle [14,17,18] with comparable conclusions. For example, a meta-analysis by Roque et al [7] included 3 trials accounting for 633 women.…”
Section: Discussionmentioning
confidence: 99%
“…A total of eight studies, all being retrospective cohort studies [35,36,[38][39][40][41][42][43], making a total of 8762 ET cycles, were included.…”
Section: Tnc Versus Ac Without Suppressionmentioning
confidence: 99%